The Impact of Human Resource Management (Hrm) Practices on Labour Productivity in Libyan National Oil Corporations: The Mediating Role of Social Skills - Mohamed Ibrahim Mohamed Abulkasim; Adel M. Abdulaziz; Mikail Ibrahim; Mahazan Abdul Mutalib @ Talib (Richtmann Publishing Ltd, 2024)
Vol. 7 No. 2